2021
DOI: 10.3390/su13041702
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Environmental and Economic Sustainability for the Building Envelope of Low-Carbon Schools

Abstract: To achieve a carbon-free economy by 2050, the construction of low-carbon schools in Italy must select the proper structural and technological solutions for the building envelope while ensuring a low economic cost. The aim of this study was to analyze and compare several technological solutions for the building envelope and the related structural solutions in terms of thermo-dynamic properties, energy performance, environmental sustainability parameters, and economic evaluations, to obtain one or more alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Cheng (2019) iterated that these systems will also enable facility managers to model and automate scheduled and predictive maintenance tasks. A positive byproduct of these systems was highlighted by Bazzocchi et al (2021), who observed other benefits derived from installing energy-efficient systems, such as reduced waste and water consumption and a decrease in labor costs.…”
Section: The Adoption Of Innovative Technologies In Commercial Propertymentioning
confidence: 99%
“…Cheng (2019) iterated that these systems will also enable facility managers to model and automate scheduled and predictive maintenance tasks. A positive byproduct of these systems was highlighted by Bazzocchi et al (2021), who observed other benefits derived from installing energy-efficient systems, such as reduced waste and water consumption and a decrease in labor costs.…”
Section: The Adoption Of Innovative Technologies In Commercial Propertymentioning
confidence: 99%
“…Life cycle assessment methodology has been applied to assess sustainability in the schools in order to calculate environmental impacts [8] including quantification of external costs [9]. Other studies open the framework also covering economic sustainability [10]. Integration of energy, water, and environment systems under the umbrella of multidisciplinary concept of sustainability and circular economy has also explored in some investigations [11][12][13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, wood fiber perfectly meets the principles of environmental sustainability and energy efficiency and can be included in a virtuous circle of recycling and circular economy [50][51][52][64][65][66]. Thus, in the past years, the employment of green materials has also grown worldwide as the green building concept [53][54][55][67][68][69].…”
Section: Introductionmentioning
confidence: 97%